ENT 530 Social Media Portfolio: Jar Coco / Hafizul Hakim Ismail - Ismail, Hafizul Hakim (2021)
The success of a small business depends on its ability to continually earn profits. Same goes to Jar Coco as we try our best in providing the best types of chocolate jar to our customers in order to attract more customers to buy our product at the same time to gain more profits and experience. First of all, Jar Coco is an online business product. The business was established on 4 May 2021. Generally, some of our customers come from different places and also from students who love chocolate fans. As presented in the company name, Jar Coco offers a familiar yet unique experience in experiencing breakfast or snacking by chocolate jar and chocolate mixed creatively with other toppings in a jar for a feast for both the eyes and the palate. Costs to be covered including various types of topping inside it. We have devised the vision, mission and logo for our Jar Coco on the grounds of functionality of our product and appeal to our target audience. Obstacles faced by Jar Coco would include competition from other food service companies in the class as well as in other classes. This competition will also be felt from other, more familiar competitors with similar ideas such as those who sell bubble rice with chocolate in jars. We hope to overcome these shortcomings in competition by offering value for money products which are significantly cheaper than the products presently available in the market. Time restraints need also be considered as the shareholders for this company are of multi-disciplinary backgrounds.